Host factors related to pneumonia in children under 5 years of age - Wiharjo Hadisuwarno; Retno Asih Setyoningrum; Pirlina Umiastuti (Indonesian Pediatric Society, 2015)
Background Pneumonia has been one of the serious problems for children under five in Indonesia. Imbalanced interactions among host factors, agents, and environments influence incidence of pneumonia. Objective To determine the risks of the host related to the incidence of pneumonia in children aged 3-59 months in Pediatrics Department, Dr. Soetomo General Hospital during 2011-2012. Methods This was a case control study on medical records of patients with respiratory infections in Pediatrics Department, Dr. Soetomo General Hospital. We grouped patients with pneumonia as the case group and patients with other respiratory infections as the control group. The data were statistically processed to calculate odds ratios and P values. Results There were 326 subjects reviewed, 163 in the case group and 163 in the control group. Host factors that increased the risk of pneumonia were: low birth weight (OR=3.10; 95%CI 1.34 to 6.86), inadequate exclusive breastfeeding (OR=1.7; 95%CI 1.09 to 2.64), malnutrition (OR=3.44; 95%CI 2.12 to 5.58) and incomplete immunization in a certain period of age (OR=2.70; 95%CI 1.72 to 4.24). Existed comorbidity was unrelated to the incidence of pneumonia (OR=1.53; 95%CI 0.86 to 2.71). Conclusion Low birth weight, inadequate exclusive breastfeeding, malnutrition, and incomplete immunization in a certain period of age increase the risk of pneumonia.